Intelligent innovation technological district for the city of Barquisimeto, diagnosis for a proposal (Gaceta Técnica, 2023)
The objective of this research is to carry out a preliminary diagnosis and analysis of the urban context in the industrial zone of the city of Barquisimeto, Venezuela, in order to detect the feasibility of making a subsequent design proposal for a technological district of intelligent innovation. To do this, a survey was applied to people who work in public and private organizations, as well as university institutions located in areas surrounding industrial zones. The application of the instrument, and the processing of the data, positioned that the proposal for a design of the intelligent innovation technological district is an offer that, in its dimension, is projected as an urban space with key infrastructure for development, innovation, the creation or technological transfer and sustainability that benefits the city. In fact, in the records and analysis provided in this work it could be seen that 80% of the selected sample maintained that the proximity between technology companies contributes to economic and social progress
Keywords: urban planification; technology district; smart innovation in industrial zones; Barquisimeto